2006
DOI: 10.1016/j.physletb.2005.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Quark spectrum above but near critical temperature of chiral transition

Abstract: We explore the quark properties at finite temperature near but above the critical temperature of the chiral phase transition. We investigate the effects of the precursory soft mode of the phase transition on the quark dispersion relation and the spectral function. It is found that there appear novel excitation spectra of quasi-quarks and quasi-antiquarks with a three-peak structure, which are not attributed to the hard-thermal-loop approximation. We show that the new spectra originate from the mixing between a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(109 citation statements)
references
References 44 publications
8
101
0
Order By: Relevance
“…Furthermore, given the qualitative differences between Refs. [304,306] and Ref. [29], the similarity between results suggests the possibility that the appearance of zero modes is model-independent.…”
Section: B Quark Spectral Density and A Sqgpsupporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, given the qualitative differences between Refs. [304,306] and Ref. [29], the similarity between results suggests the possibility that the appearance of zero modes is model-independent.…”
Section: B Quark Spectral Density and A Sqgpsupporting
confidence: 65%
“…Whilst Refs. [304,306] extract spectral densities via oneloop estimates in Nambu-Jona-Lasinio-or Yukawa-like models, the couplings are tuned to mimic a world in which chiral symmetry is dynamically broken. In this connection we re-emphasise that the zero mode appears only when the strength of the interaction is capable of producing DCSB in-vacuum; viz., when the gap equation's T = 0 kernel has sufficient support at infrared momenta.…”
Section: B Quark Spectral Density and A Sqgpmentioning
confidence: 99%
“…In Ref. 9, it is shown that the quark spectrum near T c of the chiral phase transition has three peaks through a coupling with fluctuations of the chiral condensate.…”
Section: Introductionmentioning
confidence: 99%
“…(1) in this work, the quark spectrum near T c may have the large decay width and a complicated dispersion [10,15]. It is interesting to explore mesonic excitations with such quark spectra instead of S HTL mT .…”
Section: Summary and Discussionmentioning
confidence: 96%